(untitled) (Ustozlar uchun, 2025)
Today, much attention is paid to energy saving, and at the same time, great attention is paid to quality indicators and losses of electricity in energy supply. One of the problems that are difficult to solve in electromechanical systems is the effect of transient processes that occur in electrical equipment, as a result of which the efficiency of network electrical systems decreases and various types of accidents occur. Various measures are used to solve these problems, but these methods are not effective in all cases. Therefore, when choosing a method of reducing the effect of transient processes, it is necessary to pay attention to a number of aspects of the electric conductor used. We will analyze what method is effective for using high-power equipment in terms of torque and power required during startup, and taking into account the impact on the network during startup wattage.